Nietzsche e a transvaloração da tragédia - Silva, Anildo de Souza (2014)
The main objective of this work consists in investigating, from Nietzsche’s philosophical work – especially in the texts The birth of tragedy, Human, all too human and the Genealogy of morals – in what form the contemporary esthete understood the notion of tragic art in three differentiated perspectives. For this task, we will pursue the following steps: First, the overview of the will to power and of surviving will be sketched, and the consequent affirmation of life by man. Subsequently, an understanding of the tragic art as an artist’s metaphysics will be built, perceiving it as a result of the Apollonian and Dionysian impulses, which relate to the principle of individuation and thus manifests an interpretation of the world as an aesthetic phenomenon. In this first perspective, the tragic art is useful to man by making the absurdity of life bearable. Then the second notion of tragic art as an educator of men for their most primitive instincts, mainly for the will of survival and creativity. This second way of looking at tragedy is related to an instrumental interpretation of Socratic and to Nietzsche’s “perspectivism”. Moreover, the tragic will be useful to educate man to affirm his life. In a third moment, we intend to demonstrate how tragic art, mischaracterized by modernity, shall be understood as an ascetic priestess. Finally, some concluding remarks on the problem of how tragic art has changed its meaning of artist’s methaphisics, passed to be man’s educator and became ascetic priestess. However, there is an element that will surpass all three Nietzsche’s notions of tragic art, namely its usefulness in seducing men to affirm their living.